SOSIALISASI UU NO 7 TAHUN 2021 TENTANG HARMONISASI PERATURAN PERPAJAKAN PADA UMKM DI WILAYAH SAMBIROTO SEMARANG - Apip; Dul Muid; Clara Yully Diana Ekaristi; Hamdani (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
Sambiroto Village, Tembalang District, Semarang is an area that is being targeted by entrepreneurs and the MSME community. What is of concern is that entrepreneurs and MSMEs in the Sambiroto Region do not fully understand Law number 7 of 2021 concerning the Harmonization of Tax Regulations. Therefore, service activities were held by conducting socialization to provide an understanding of taxation on taxpayer compliance. The activity takes place from February-June 2022. The target of this activity is MSMEs in the Sambiroto Region. The method of implementing Community Service includes socialization and discussion regarding the provisions of the tax on Non-Taxable Income or Taxable Income for MSMEs. The results of the activity are that the MSME community gets information, knowledge of how the government takes sides with Micro, Small and Medium Enterprises through fiscal policy.